TEORI BERMAIN DAN PSIKOLOGI ANAK USIA DINI (AUD): MEMAHAMI DUNIA ANAK MELALUI AKTIVITAS BERMAIN DI RA AM-MENTARI KOTA JAMBI - Jamilah; Mujapasa, Hannafirsta Seroja; Apriliana, Dewanti; Anggraini, Leza; Putri, Regina Adinda; Shalsadila, Rischa Dwi; Witdia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the importance of understanding play theory and early childhood psychology in supporting holistic child development through meaningful play activities. The problem addressed in this community service activity is the limited understanding among educators and parents regarding the alignment between children’s play activities and their psychological developmental needs, which often results in rigid and inappropriate learning approaches. This activity aimed to improve the understanding of school principals, teachers, educational staff, and parents about the significance of play-based learning in early childhood education. The program was conducted at RA AM Mentari, Jambi City, on May 14, 2026, using psychoeducational seminar methods, interactive discussions, and problem-based learning approaches. The speakers presented classical and modern theories of play, stages of social play development, and practical strategies for implementing psychologically healthy play activities. The results showed increased awareness, enthusiasm, and understanding among participants in designing educational, enjoyable, and meaningful play activities both at school and at home. The activity also encouraged collaboration between teachers and parents in creating a child-friendly learning environment that supports children’s cognitive, social-emotional, language, physical-motor, and moral-spiritual development in a holistic manner.